To the issue of differential diagnosis of listeriosis - O. V. Kladova; A. E. Andzhel; Yu. V. Kompaniets; N. L. Grishkevich (LLC "Diagnostics and Vaccines", 2019)
A clinical example shows the erroneous diagnosis of listeriosis in a 15-year-old child hospitalized in the infectious department. The child was admitted with severe symptoms of intoxication, febrile fever, difficulty in nasal breathing, hyperemia of the mucous membranes of the oropharynx, tonsillitis, cervical lymphadenitis, facial tissue pasteness with swelling of the eyelid and conjunctivitis of the left eye, hepatosplenomegaly. A laboratory examination revealed pronounced leukocytosis up to 24 thousand, lymphocytosis, atypical mononuclear cells up to 9%, IgM and IgG to EBV capsid protein, IgM to CMV, IgM and IgG to listeria. But with a repeated double study of IgM and IgG to Listeria were not detected. The initial positive result was possibly due to the presence of cross-reacting antibodies in EBV mononucleosis. The final diagnosis was made: Infectious mononucleosis of mixed (EBV, CMV) etiology. Chronic polypous rhinosinusitis, exacerbation. Reactive edema of the eyelids against the background of inflammation of the sinuses.Given the variety of clinical forms of listeriosis and their similarity with the manifestations of other infections, for the full diagnosis of listeriosis infection, it is advisable to evaluate the epidemiological and medical history data, as well as use an extended spectrum of laboratory confirmation of the diagnosis.